High-Resolution X-Ray Computed Tomography: A New Workflow for the Analysis of Xylogenesis and Intra-Seasonal Wood Biomass Production - Lehnebach, Romain; Campioli, Matteo; Gričar, Jozica; Prislan, Peter; Mariën, Bertold; Beeckman, Hans; Van den Bulcke, Jan (Frontiers in Plant Science, 2021)
Understanding tree growth and carbon sequestration is of crucial interest to forecast the feedback of forests to climate change. To have a global understanding of wood formation, it is necessary to develop new methodologies for xylogenesis measurements, valid across diverse wood structures and applicable to both angiosperms and gymnosperms. We present here a new workflow to study xylogenesis using High-Resolution X-ray Computed Tomography (HRXCT), which is generic and offers high potential for automatization. The HXRCT-based approach was benchmarked with the current classical approach (microtomy) on three tree species with contrasted wood anatomy (Pinus nigra, Fagus sylvatica and Quercus robur). HRXCT proved to estimate the relevant xylogenesis parameters (timing, duration and growth rates) across species with high accuracy. HRXCT showed to be an efficient avenue to investigate tree xylogenesis for a wide range of wood anatomies, structures and species. HRXCT also showed its potential to provide quantification of intra-annual dynamics of biomass production through high-resolution 3D mapping of wood biomass within the forming growth ring.